Workplace violence victimization in young workers: An analysis of the US National Crime Victimization Survey, 2008 to 2012. Issue 8 (20th June 2019) - Toussaint, Maisha; Ramirez, Marizen R.; Peek‐Asa, Corinne; Saftlas, Audrey; Casteel, Carri
Abstract: Background: The aim of this study was to measure the frequency of workplace violence (WPV) victimization in 16 to 24‐year olds in the United States and compare rates by occupation and demographics. Methods: As an open cohort, participants 12 years or older in the National Crime Victimization Survey were interviewed at 6‐month intervals over a 3‐year period from 2008 to 2012. WPV victimization rates were calculated. Weighted, multilevel Poisson regression was used to compare WPV victimization rates by occupation and demographics. Results: The rate of WPV victimization was 1.11 incidents per 1000 employed person‐months (95% confidence interval: 0.95‐1.27). The highest rates of WPV were in protective service occupations (5.24/1000 person‐months), transportation (3.04/1000 person‐months), and retail sales (2.29/1000 person‐months). Compared with their respective counterparts, lower rates of WPV victimization were found among younger, black, and rural/suburban workers. Conclusions: Findings identify occupations and target populations in need of future research and evidence‐based interventions to improve the working conditions for young workers.